"You only have time for so much in 12 hours" unmet social needs of hospitalised patients: A qualitative study of acute care nurses. Issue 19 (26th June 2019) - Brooks Carthon, J. Margo; Hedgeland, Taylor; Brom, Heather; Hounshell, Danielle; Cacchione, Pamela Z.
Abstract: Aims and objectives: To explore the experiences of nurses caring for socially at‐risk patients and gain an understanding of the challenges nurses face when providing care. Background: Nurses play a pivotal role in caring for hospitalised patients with social risk factors and preparing them for discharge. Few studies have explored whether acute care nurses are adequately supported in their practice environments to address the unique needs of socially at‐risk patients as they transition back into community settings. Design: A qualitative descriptive study of nurses working in a large urban academic medical centre. Methods: We conducted six semi‐structured focus groups of nurses ( n  = 21). Thematic content analysis was performed to analyse the transcripts from the focus groups. We adhered to COREQ guidelines for reporting this qualitative study. Results: Six key themes emerged: (a) nurses' assessments of social risk factors, (b) experiences providing care, (c) barriers to care, (d) fear of "labelling" socially at‐risk patients, (e) unmet social care needs and (f) recommendations to improve care. Conclusions: Our findings suggest that nurses are able to identify social risk factors. However, prioritisation of medical needs during acute care hospitalisation and lack of organisational supports may deter nurses from fully addressing social concerns. Relevance to clinical practice: Acute care nurses should be involved in the development of future efforts to address the needs of socially at‐risk patients and be provided with additional supports in their practice environments. This could include continuing education to build nursing competencies in community‐based care and social vulnerability.